Commitment and cooperation on high courts : a cross-country examination of institutional constraints on judges - Alarie, Benjamin; Green, Andrew James (Oxford University Press, 2017)
This work explains how the answers to the following institutional questions largely determine the influence of political preferences of individual judges and the degree of cooperation among judges at a given point in time.